Masalah Akuntabilitas Publik Pada Organisasi Pemerintah (Studi pada Organisasi Perangkat Daerah Pemerintah Kota Tegal) - Niode, Narapati Abharina Kibran; Yusuf, Muhammad (UNIB Press, 2021)
The phenomenon that occurs in the public sector in Indonesia is the strengthening of demands for accountability in government organizations, both central and regional. According to Indonesia Corruption Watch, the City of Tegal is ranked first in Central Java in cases of accounting fraud that have caused losses to state finances. This shows the problem of public accountability in the City Government of Tegal. This study aims to obtain empirical evidence regarding the influence of internal control systems, organizational commitment, organizational culture, budgetary participation and management accounting information systems on public accountability. The study was conducted on 19 OPDs in Tegal City. The data analysis technique used is multiple linear regression. The results showed that the internal control system, organizational culture and budgetary participation had a positive effect on public accountability. Meanwhile, organizational commitment and management accounting information system have no effect on public accountability. The contribution of this study provides empirical evidence that the internal control system, organizational culture and budgetary participation are factors that influence public accountability.